The application of insurance as a tool for mitigating the effects of drought in agriculture - Burgaz F.J. (Drought management: scientific and technological innovations, 2008)
Many management models and instruments have been devised in the farming sector in response to the traditional uncertainty that has characterized agricultural activity since its origins. Starting from informal organization models, in recent years we have arrived at the use of insurance as the most effective tool for mitigating the risks arising from drought events. This text describes the benefits for rural society and a country's economy as a whole of the availability of insurance, and the requirements that should apply to an insurance model in order to achieve the best results. After defining the various instruments available for managing losses caused by drought, we review the results achieved in Spain in the development of drought insurance. The greater the development in agriculture, the more possibilities there will be for the implementation of insurance models, and in this respect, there are currently good prospects in the EU context.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)